Strengthening Students' Religious Character in Muhammadiyah Elementary Classroom: Peningkatan Karakter Keagamaan Siswa di Kelas Sekolah Dasar Muhammadiyah - Nazilah, Nurun; AMRULLAH, MUHLASIN (Indonesian Journal of Education Methods Development, 2025)
General Background: Religious character development in elementary education is essential for forming students’ moral and spiritual foundations. Specific Background: In the context of SD Muhammadiyah, classroom-based approaches integrate character values into daily learning activities aligned with the curriculum. Knowledge Gap: While character education programs exist, limited studies examine structured classroom-based implementation and its effect on students’ religious behavior. Aim: This study aims to explore strategies for strengthening students’ religious character through classroom-based learning. Methods: A qualitative approach was employed using observations, interviews, and document analysis with school principals, teachers, and students as participants. Data were analyzed through data collection, reduction, presentation, and conclusion drawing, with data validity ensured via source triangulation. Results: Findings indicate that embedding religious values into subject learning fosters a supportive environment for character development. Structured lesson modules under the Merdeka Curriculum facilitate daily application of these values, though ongoing evaluation is necessary to ensure consistent implementation. Novelty: This study provides insights into practical classroom-based strategies for reinforcing religious character in elementary education. Implications: The findings offer guidance for educators to integrate religious values effectively into learning processes, contributing to holistic student development. Highlights: Integration of religious values into daily classroom activities. Structured lesson modules under the Merdeka Curriculum. Need for continuous evaluation to sustain effectiveness. Keywords: Religious Character, Classroom-Based Learning, Elementary Education, Character Education, Merdeka Curriculum